FAKTOR-FAKTOR PENANDA KESANTUNAN TUTURAN IMPERATIF DALAM BAHASA JAWA DIALEK SURABAYA: ANALISIS PRAGMATIK - Bea Anggraini (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
This paper attemps to describe politeness strategies found in imperative of Javanese language in Surabaya . This is a descriptive and qualitative study under the scope of pragmatics . Linguistically, markers of politeness may be seen in the differences of long and short utterances, intonation and speech hiearchy: non-imperative such as declarative and interrogative forms are examples of pragmatic politeness .